Analisis Kebutuhan Pengembangan E-Modul Pembelajaran Sejarah Lokal Jalur Rempah di Minangkabau - Iskandar, Meisya Alifa; Aisiah, Aisiah (Jurnal Kronologi, 2024)
Abstract : This research aims to map the needs for developing E-Modules for local history learning on the Spice Route in Minangkabau in history subjects in high school phase E (class X) from the aspect of analyzing curriculum needs, teacher needs and student needs. The research method uses a quantitative and qualitative descriptive approach (Mix Methods). The research data sources come from curriculum documents, teachers and students. The types of data collected are quantitative data and qualitative data related to the analysis of the needs for developing an E-Module on the local history of the spice route in Minangkabau. Data collection techniques were carried out using questionnaires (quantitative data) and by observation and interviews (qualitative data). Data analysis was carried out quantitatively using percentages (%) and descriptively qualitatively. The general research findings are that teachers and students need learning resources in the form of E-Modules about the local history of the spice route in Minangkabau. The specific research finding is that the E-Module on the local history of the Spice Route in Minangkabau is needed by high school teachers and students. History learning e-modules are needed to meet curriculum demands. The Independent Curriculum requires local history to be taught as stated in the History Learning Outcomes. History teachers need the Minangkabau Spice Route local history E-Module. Students also need a local history E-Module to support history learning in implementing the independent curriculum. It is hoped that the e-module that will be developed can help teachers and students understand the Spice Route in Minangkabau. Keywords: E-Module, Spice Route, History Learning, Minangkabau Abstrak : Penelitian ini bertujuan untuk memetakan kebutuhan pengembangan E-Modul pembelajaran sejarah lokal Jalur Rempah di Minangkabau pada mata pelajaran sejarah di SMA fase E (kelas X) dilihat dari aspek analisis kebutuhan kurikulum, kebutuhan guru dan kebutuhan peserta didik. Metode penelitian menggunakan pendekatan deskriptif kuantitatif dan kualitatif (Mix Methods). Sumber data penelitian berasal dari dokumen kurikulum, guru dan siswa. Jenis data yang dikumpulkan yakni data kuantitatif dan data kualitatif terkait analisis kebutuhan pengembangan E-Modul sejarah lokal jalur rempah di Minangkabau. Teknik pengumpulan data dilakukan dengan menggunakan kuesioner (data kuantitatif) dan dengan cara observasi maupun wawancara (data kualitatif). Analisis data dilakukan secara kuantitatif menggunakan persentase (%) dan secara deskripsif kualitatif. Temuan penelitian secara umum guru dan siswa membutuhkan sumber belajar dalam bentuk E-Modul tentang sejarah lokal jalur rempah di Minangkabau. Temuan khusus penelitian yakni E-Modul sejarah lokal Jalur Rempah di Minangkabau dibutuhkan oleh guru dan siswa SMA. E-Modul pembelajaran sejarah dibutuhkan untuk memenuhi tuntutan kurikulum. Kurikulum Merdeka mensyaratkan adanya sejarah lokal yang harus diajarkan seperti yang tertuang dalam Capaian Pembelajaran Sejarah. Guru sejarah membutuhkan E-Modul sejarah lokal Jalur Rempah Minangkabau. Siswa juga membutuhkan E-Modul sejarah lokal untuk menunjang pembelajaran sejarah dalam implementasi kurikulum merdeka. E-Modul yang akan dikebangkan diarapkan dapat membantu guru dan siswa dalam memahami Jalur Rempah di Minangkabau. Kata Kunci : E-Modul, Jalur Rempah, Pembelajaran Sejarah, Minangkabau